Utilization of Functional Food Based on Breadfulness (Artocarpus Altilis) as A Source of Antioxidants in Diabetes Mellitus: Literature Review - Ayu Putri; Helmizar Helmizar; Syahrial Syahrial (GLOBAL HEALTH SCIENCE GROUP, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia due to impaired carbohydrate, protein, and fat metabolism. One common symptom experienced by sufferers is polyphagia (increased hunger) caused by impaired energy utilization due to suboptimal insulin function. Furthermore, oxidative stress resulting from high blood sugar levels can exacerbate insulin resistance. Therefore, the use of functional foods high in antioxidants is a potential strategy for diabetes management. Breadfruit (Artocarpus altilis) is known to contain bioactive compounds such as flavonoids, polyphenols, and quercetin, which have antioxidant activity. This study aims to assess the potential of breadfruit as a functional food source of antioxidants in the management of diabetes mellitus based on the results of recent research. This study employed a literature review to examine the utilization of breadfruit (Artocarpus altilis) as a functional food rich in antioxidants for the management of diabetes mellitus. Data were obtained from Google Scholar, ScienceDirect, and PubMed using the keywords “functional foods,” “breadfruit,” “Artocarpus altilis,” “antioxidants,” “diabetes mellitus,” “oxidative stress,” and “hyperglycemia,” with a publication period limited to 2020–2025. Articles were then screened based on relevance, full-text availability, and suitability with the research objectives. A total of 45 articles were identified, of which 20 met the inclusion criteria, and 4 articles were analyzed further. The review showed that breadfruit leaf extract was able to lower triglyceride levels and increase total sperm count in diabetic rats. Furthermore, breadfruit pulp extract was shown to lower blood glucose levels. The combination of breadfruit flour and red bean flour also has the potential to modulate the atherogenic index in diabetic rats. The therapeutic mechanisms of breadfruit are thought to involve antioxidant activity, increased insulin sensitivity, and modulation of lipid metabolism. Breadfruit has potential as a functional food to help control diabetes mellitus and its complications. However, further research is needed to determine the optimal dosage, safety, and molecular mechanisms in greater depth.